The English Teacher’s Strategies in Teaching English by Online (A Research Conducted at SMAN 1 Gorontalo) - T. Miolo, Sartin; Sabouw, Elsje Louise; Bahansubu, Nurfitti (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
Pandemic Covid19 attacked the education site by giving a limitation in the learning process which is without direct instruction between student and teacher. It caused teacher and student used the learning activities that make it possible to carry out learning using internet access through online learning. In the fact there are so many obstacles faced by English’ teacher also student in online learning such as the bad internet connection and the lack of internet quota for student also the decreased of student’ attendance. Qualitative method aims to investigates to understand and explores a phenomenon carried out by teacher in online learning especially to aims the strategies used by teacher in online learning. The subjects were four EFL teacher who were teaching during pandemic. The theory about learning strategies was used in this study to analyze the data.Moreover this study employed an interview technique to obtain the supporting data about English teacher’s strategies in teaching English by online. The result shows that several strategies used by English teacher for instance by using Google classroom, Quiper and agreement and also several obstacles such as internet connection, internet quota and students atandance.